Perbedaan Kejadian Asfiksia Neonatorum pada Kehamilan dengan Preeklamsia Ringan dan Kehamilan Normal di RSUD Dr. Moewardi Surakarta - Hadiyanto, Louis; Darto, .; Hafidha, Nur Hafidha (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2013)
Background: The incidences of early neonatal death and stillborn are high despite decreased overall child mortality rate. Asphyxia is one of causes of neonatal deaths. Hypertension in pregnancy (preeclampsia) may contribute to perinatal morbidity and mortality. Placental ischemia is proposed to be cause of preeclampsia as well as mechanism leading to neonatal asphyxia. This study aimed to compare the prevalences of neonatal asphyxia in pregnancies with mild preeclampsia and normal pregnancy at RSUD Dr. Moewardi Surakarta. Methods: This was an observational analytic study with cross-sectional approach, conducted from April to August 2012. Thirty patients with mild preeclampsia and 30 patients with normal pregnancies were selected based on certain criteria. Preeclampsia patients were identified from signs of hypertension (systolic/diastolic blood pressure â¥140/90 mmHg), extremity edema, and/or proteinuria. Neonatal asphyxia was identified from APGAR scores documented in medical record. Data were analyzed by Fisherâs exact test using SPSS version 13.0 for Windows. Results: Only 1 (3.3%) case of neonatal asphyxia was found in pregnancy with mild preeclampsia. No neonatal asphyxia was found in normal pregnancy. Result fromÂ Fisherâs exact test showed a p-value of 1.000 (p>0.05). Conclusion: There was no difference of neonatal asphyxia prevalence in pregnancies with mild preeclampsia and normal pregnancy at RSUD Dr. Moewardi Surakarta. Keywords: Mild preeclampsia, normal pregnancy, neonatal asphyxia